2017
DOI: 10.1186/s12970-017-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-fatigue property of the extruded product of cereal grains mixed with Cordyceps militaris on mice

Abstract: BackgroundFatigue is a biological phenomenon that involves a feeling of extreme physical or mental tiredness that could potentially cause some severe chronic diseases. Recently, diet therapy has provided a new alternative to alleviate physical fatigue. In our previous study, addition of Cordyceps militaris (C. militaris) into an extruded product was shown to provide high nutrition and unique flavors; however, little is known whether this product has some scientific evidence regarding anti-fatigue property. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…The lowest value of lactate was noted in rats supplemented simultaneously with A and either Cr form. These results confirm the antifatigue During exhaustive exercise, ATP is consumed continuously by myocytes, which can be generated through oxidative phosphorylation in the muscle (60). Under this condition, glycogen is converted into glucose to generate ATP (61), resulting in a depletion of glycogen storage in the liver and muscles (62).…”
Section: Discussionsupporting
confidence: 76%
“…The lowest value of lactate was noted in rats supplemented simultaneously with A and either Cr form. These results confirm the antifatigue During exhaustive exercise, ATP is consumed continuously by myocytes, which can be generated through oxidative phosphorylation in the muscle (60). Under this condition, glycogen is converted into glucose to generate ATP (61), resulting in a depletion of glycogen storage in the liver and muscles (62).…”
Section: Discussionsupporting
confidence: 76%
“…Under normal conditions, muscular LDH catalyzes the mutual transformation of LA and pyruvate (24). High serum LDH levels are also a marker of muscle damage (27). The present study demonstrated that TM possesses anti-fatigue properties, as 1.0 g/kg TM treated female mice exhibited significantly reduced serum LA and LDH levels.…”
Section: Discussionmentioning
confidence: 52%
“…LA serum levels in males remained unchanged following treatment with all doses of TM. In addition, excessive quantities of LDH serve as an indicator of muscle damage (27). Following 30 min exercise, a 14-day treatment of 1.0 g/kg TM reduced serum LDH levels by 15.9 and 11.4% in female and male mice respectively compared with the control (both P<0.05; Fig.…”
Section: -Day Drug Treatmentmentioning
confidence: 99%
“…Cordyceps militaris has been used as an edible and medicinal mushroom in many countries throughout East Asia and Southeast Asia over a period of several centuries (Xia et al, ; Zhong et al, ). Extensive studies have demonstrated the various biological and pharmacological functions of C. militaris , such as anti‐inflammatory, antitumor, anti‐diabetes, and anti‐oxidation (Das, Masuda, Sakurai, & Sakakibara, ; Dong et al, ), and so forth.…”
Section: Introductionmentioning
confidence: 99%